Surface modification induced by perovskite quantum dots for triple-cation perovskite solar cells. (January 2020) - Yang, Wenqiang; Su, Rui; Luo, Deying; Hu, Qin; Zhang, Feng; Xu, Zhaojian; Wang, Zhiping; Tang, Jialun; Lv, Zhao; Yang, Xiaoyu; Tu, Yongguang; Zhang, Wei; et al.
Abstract: Organic-inorganic hybrid perovskite solar cells are regarded as the most promising new-generation photovoltaic technology, owing to their high power conversion efficiencies and low cost. However, surface imperfections of perovskite films impede improvement in device performances, since surface imperfections can introduce undesired energy losses under sunlight illumination. Here, we show that the incorporation of zero-dimensional perovskite quantum dots into three-dimensional perovskite films can heal surface imperfections in perovskite films. Introducing perovskite quantum dots also leads to a more uniform surface topography and potential, along with an improved crystal quality of the triple-cation perovskite films, benefiting charge carrier kinetics between the perovskite films and the charge extraction layers. Ultimately, we achieve a power conversion efficiency exceeding 21% in triple-cation perovskite solar cells. Graphical abstract: Image 1 Highlights: Perovskite quantum dots as passivation agents was applied in triple-cation perovskite solar cells. The surface morphology, electronic properties and crystal structure of perovskite film were modified synergistically. Undesired imperfection on the surface of the perovskite films were eliminated. Triple cation perovskite solar cells with PCEs exceeding 21% without post-treating process were achieved.